2010
DOI: 10.1111/j.1460-9568.2010.07402.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of CXCR4 function in μ‐opioid receptor‐deficient glia

Abstract: The chemokine receptor CXCR4 and the μ-opioid receptor (MOR) are G-protein-coupled receptors (GPCRs) essential to normal function of the nervous and immune systems. Several studies suggest that MOR is a key regulator of CXCR4 in the brain; however, the molecular basis of the opioid/chemokine interaction are not fully understood and may involve different mechanisms in neuronal and glial cells. Our previous studies demonstrated that MOR stimulation specifically up-regulates the protein ferritin heavy chain (FHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…This could be related to the fact that neuronal and glial cells both express opioid receptors in cell membranes (Bokhari et al, 2009;Burbassi et al, 2010;Kao et al, 2012) that are able to bind the ( À ) but not the ( þ) isomers of endogenous and exogenous opioids (agonists or antagonists). ( þ) Naloxone cannot bind to neuronal opioid receptors, and does not induce hyperalgesia on day 21, but induced significant astrocyte re-activation in the spinal cord (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the fact that neuronal and glial cells both express opioid receptors in cell membranes (Bokhari et al, 2009;Burbassi et al, 2010;Kao et al, 2012) that are able to bind the ( À ) but not the ( þ) isomers of endogenous and exogenous opioids (agonists or antagonists). ( þ) Naloxone cannot bind to neuronal opioid receptors, and does not induce hyperalgesia on day 21, but induced significant astrocyte re-activation in the spinal cord (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocyte opioid receptor expression is by far the best defined, including expression of (Dobrenis et al, 1995;Hauser et al, 1996;Ruzicka et al, 1996;Festa et al, 2002;Burbassi et al, 2010), (Bunn et al, 1985;Gorodinsky et al, 1995;Maderspach et al, 1995), and ␦ receptors (Thorlin et al, 1998a). However, this opioid receptor expression is highly varied.…”
Section: Central Anatomical Locations Of Opioid Analgesic Action and mentioning
confidence: 99%
“…Recently, our group has shown that morphine (and selective μ-opioid receptor [MOR] agonists, such as DAMGO) specifically impairs CXCL12/CXCR4 signaling in neurons, both in vitro and in vivo, by increasing protein levels of ferritin heavy chain (FHC), a recently described CXCR4 regulator (25,(27)(28)(29). Morphine increases the level of FHC and its association with CXCR4, thereby inhibiting CXCR4 activation and downstream prosurvival signaling pathways (27).…”
Section: Introductionmentioning
confidence: 99%